Insights into the role of the liquid-liquid interface in biphasic reactions: the reaction of vitamin B12s(aq) with vicinal dibromides(oil). - Davies, T; Garner, A; Davies, S; Compton, R (2005)
Electrocatalytic processes can take place either homogeneously in a single liquid phase or heterogeneously at the liquid-liquid interface formed in emulsions. This Article addresses the question as to whether a change in rate and/or mechanism can occur between the two possibilities. Specifically, cyclic voltammetry and electrosynthetic experiments are used to demonstrate that for the vitamin B12 mediated reduction of vicinal dibromides producing olefins, electric field effects likely operate at the liquid-liquid interface which can change the populations of different conformers relative to the single homogeneous-phase experiment, leading to significant changes in rate.